Mitigasi Bencana Banjir pada Bangunan Sekolah Melalui Tata Lanskap - Kahar Sunoko; Amin Sumadyo; Agung Kumoro W; Akhmad Farkhan (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
Vulnerability to flood hazards occurs at SD Iroyunan, Pajangan, Bantul, which is located in the Bedog river watershed and the landscape pattern of the area is quite steep. The morphology of the area indicates that its development lacks insight into the potential for flooding and on sustainable landscape management. This phenomenon shows that there is a gap, so it is necessary to study the landscape. The study was carried out in a descriptive exploratory manner, to obtain a detailed description of the landscape pattern and vulnerability of the school site area. This study resulted in findings about patterns of landscape vulnerability and school landscape models in flood disaster preparedness.